LOS ESTUDIOS DE LAS MUJERES Y DE GÉNERO EN CENTROAMÉRICA Y CHIAPAS: AVANCES Y DESAFÍOS (1957-2015) - Rodríguez Sáenz, Eugenia (2019)
This article analyzes, based on a sample of the main academic production, what are the most important tendencies and advances that women’s and gender studies have experienced in Central America and Chiapas, during the twentieth and the beginning of the twentieth one centuries. Besides, it will be established what are some of the most relevant challenges that face the development of women’s and gender studies, and particularly of women’s and gender history at regional level.